DNA damage-inducible origins of DNA replication in Escherichia coli. - Magee, T R (1992)
Upon induction of the SOS response in Escherichia coli, the mode of initiation of DNA replication is altered such that it can occur in the absence of normally required protein synthesis. This type of DNA replication has been termed induced stable DNA replication (iSDR). We examined the origin usage during iSDR and found that the initiation of iSDR occurs primarily in the oriC and terC regions of the chromosome in a manner completely independent of transcription, translation and DnaA protein. Minichromosomes (oriC plasmids) pOC23 and pOC81 were induced to replicate in the absence of DnaA protein and transcription after SOS induction. The results localized one of the iSDR origin activities in a 596 bp region which includes the minimal oriC.